Utilization of functionally graded materials in femoral prosthesis / Azim Ataollahi Oshkour - Azim Ataollahi, Oshkour (2015)
Total hip replacement is a highly effective surgical operation that relieves pain and restores the function of a degenerated hip joint. However, with the increasing incidence of total hip replacements, particularly among young patients, and femoral prosthesis implantation, implant designs should consider long-term survival and better performance. Minimizing the mismatch between the prosthesis and bone stiffness to reduce stress shielding and retain interface stresses within acceptable levels, can increase the longevity of total hip replacement and enhance the performance of the prosthesis. A prosthesis with adjustable stiffness may enable prosthetists to match the prosthesis and bone stiffness. Functionally graded materials have attracted much attention in the production of prosthesis with customizable stiffness. Computational modeling provides a flexible framework to examine the behavior of hip replacements, host bone, and different implant design configurations using a computer instead of conducting expensive and destructive experimental tests. ABAQUS, a finite element software, was used to analyze a femur implanted with different prostheses and determine the circumferential crack behavior in the cement layer of a total hip replacement. The cemented and cementless Charnley femoral prostheses composed of functionally graded materials were initially examined. Finite element analysis was performed on the implanted femur with prostheses made of conventional materials, such as stainless steel, and titanium alloys. Finite element analysis was then conducted on the cementless and cemented functionally graded femoral prostheses with different geometries. Circumferential cracks were located in the cement layer on the internal and external surfaces of the cement at different positions along its length from distal to proximal direction. After numerical studies, an experiment was performed using the composites and functionally graded materials composed of four metallic phases and two ceramic phases. Physical and compressive mechanical properties were then examined. Results revealed that a prosthetic material plays a key role on the strain energy density in the proximal metaphysics of the femur and on the stress distribution in the implanted femur constituents. Low-stiffness prostheses resulted in higher strain energy density in the periprosthetic femur. In the femur with functionally graded prostheses, strain energy density proportionally increased with gradient index growth. Stiffer prostheses carried more stress than less stiff prostheses. The increase in gradient index also showed an adverse relationship with the developed stress in the femoral prostheses. However, the developed stress in the bone and cement demonstrated an increasing trend with the increase in gradient index. The internal and external circumferential cracks had no significant interaction. The numerical study on the circumferential crack behavior revealed that KII was smaller than KI and KIII. Higher values of stress intensity factors were obtained at the distal part compared with that at the proximal part of the cement layer. Moreover, experimental results revealed that the abundant metallic and ceramic composites showed better mechanical properties than those of the composites with 40 wt%–60 wt% of the metal and ceramic phases. In addition, compared to pure metals, the functionally graded materials exhibited better mechanical properties, such as low Young’s modulus. Functionally graded materials also demonstrated more compressive stress and plastic deformation than the composites with more than 30 wt% ceramic phases.